Modelling of dye adsorption from aqueous solution on polyaniline/carboxymethyl cellulose/TiO2 nanocomposites - Tanzifi, M.; Tavakkoli Yaraki, M.; Karami, M.; Karimi, S.; Dehghani Kiadehi, A.; Karimipour, K.; Wang, Shaobin (Academic Press, 2018)
In the present study, a polyaniline/carboxymethyl cellulose/TiO2 nanocomposite (PAn/CMC/TiO2) was synthesized by a polymerization method, and was used for adsorption of Congo Red from aqueous solution. The effects of operational parameters of the adsorption process including pH, initial dye concentration, temperature, adsorbent dosage, and adsorption time on adsorption efficiency were investigated, and response surface methodology was used for their optimization. Optimal adsorption conditions were determined at pH of 2.6, initial concentration of , temperature of 56 °C, adsorption time of 24 min, and adsorbent dose of 0.14 g. In addition, the system was also simulated using artificial neural network (ANN) and genetic programming (GP). It was found that the behavior of the system could be well predicted by ANN using 5, 1 and 8 neurons for input, middle and output layers, respectively. Kinetic and isothermal analyses showed that the maximum adsorption capacities were obtained at 94.28, 97.53 and 119.9 by Langmuir model at temperatures of 25, 40 and 50 °C, respectively and that adsorption kinetics followed the pseudo-second-order model. The nano-adsorbent was also found to be reusable without a significant change in adsorption capacity for at least five adsorption-desorption cycles. Finally, the mechanism of dye adsorption on the nano-adsorbent was investigated and proposed.